USING COOPERATIVE LEARNING IN TEACHING NARRATIVE TEXT TO IMPROVE STUDENTS’ ABILITY IN READING COMPREHENSION - Nor, Hidayah (LET: Linguistics, Literature and English Teaching Journal, 2013)
In this study, the writer tried to teach English (reading skill) to the eighth grade students of Junior high school. The reading material that the writer taught was Narrative text based on the syllabus of English subject at the eighth grade level students. I tried to solve the problem of the eighth grade students of junior high school in reading skill particularly in this case to improve their ability in understanding narrative text. In narrative text, the students should know about generic structure (Orientation, Complication, and Resolution), language features of narrative text (using simple past tense), and also the students can get new vocabulary in learning narrative text. Finally, students are able to answer the questions based on the text correctly. This study using cooperative learning, means students working together to accomplish shared goals. Within cooperative activities individuals seek outcomes that are beneficial to themselves and beneficial to all other members.